Gaussian Integer Solutions Of The Diophantine Equation ^ + ^ = ^ For X Not Equal To Y - Shahrina Ismail; Kamel Ariffin Mohd Atan; Diego Sejas-Viscarra; Kai Siong Yow (College of Science for Women/ University of Baghda, 2024)
Vol. 14 No. 3 (2017) Page(1-16)